Influence of Adiposity on Physical Activity in Schoolchildren: The Moderator Role of Adherence to the Mediterranean Diet - Garcia-Hermoso, A (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
Background: Studies were performed in order to determine the existing relationship between body composition and both physical activity (PA) levels and food habits. Nevertheless, no study has yet examined if the association between adiposity and PA in children is moderated by adherence to the Mediterranean diet (MD). Methods: the cross-sectional and associative analysis involved a total of 370 children (55.1% boys) aged 6-13, from six different schools from the Murcia region of Spain. Results: The different values of moderator [adherence to the MD expressed as a Mediterranean Diet Quality Index (KIDMED) score] are shown by the slope and the different areas of significance. The first area was shown below ≤3.8, indicating that the unfavorable influence of excess of adiposity on PA could be intensified for children in this area. The second area was a significant positive area was shown above ≥9.3, expressing that the unfavorable influence of adiposity could be reduced for those who were above this estimation point. Conclusion: Our findings reveal that the adverse effects of excess adiposity on PA can be moderated by adherence to the MD among schoolchildren. © 2020 by the authors.